Sigmoid sinus resurfacing technique for management of sigmoid sinus dehiscence causing pulsatile tinnitus: a case report - Ishak, Azlan Iskandar; Mohamed, Mohd Hazmi; Narayanan, Prepageran (Universiti Putra Malaysia, 2023)
A 33-year-old female presented with persistent and troublesome right tinnitus two months after receiving a booster dose of the COVID-19 vaccine. She noticed the tinnitus to be pulsatile, disappearing whenever she lay in bed with the right side of her head on a pillow. She had no hearing loss, history of ear infections, or complaints of neurological dysfunction. Upon examination, gentle pressure applied on the right side of the neck would make the tinnitus cease completely. A computed tomography (CT) scan of the temporal bone suggested sigmoid sinus dehiscence (SSD). Without obliterating the sigmoid sinus, a transmastoid resurfacing of the SSD was done with bone wax and a temporalis fascia graft. This technique has proven effective in relieving tinnitus in our case. The patient was reported to be tinnitus-free following the procedure.